Pengaruh Etika Pemasaran Islami dan Kualitas Layanan Terhadap Loyalitas Pelanggan Fashion Muslim E-Commerce Shopee dengan Kepuasan Sebagai Variabel Mediasi - Akmala, Zakia; Ridlwan, Ahmad Ajib (Jurnal Ekonomika dan Bisnis Islam, 2022)
The e-commerce industry plays a significant part in the consumption behavior of the Indonesian Muslim community. Both business actors and consumers take advantage of the presence e-commerce in buying and selling transactions. Business actors should carry out the principles of muamalah according to the teachings of the Prophet Muhammad SAW. Satisfaction as a mediating variable, this study intends to identify the influence of Islamic marketing ethics and service quality on customer loyalty of Msulim fashion e-commerce Shopee among Surabaya City Students. This study tested the measurement and structural models using the PLS-SEM technique. Purposive sampling was used as a sampling technique to get 100 respondents. This study explains that Muslim fashion e-commerce Shopee customer loyalty is influenced by Islamic marketing ethics, service quality and satisfaction. Satisfaction mediates the influence between service quality and customer loyalty. However, satisfaction does not mediate the relationship between Islamic marketing ethics and customer loyalty. This study provides managerial implications for Shopee companies to have a better understand that Islamic marketing ethics, service quality and satisfaction are very important to encourage the emergence of loyalty behavior and the significant role of e-commerce customers in increasing the income of business actors in Shopee e-commerce.